Interest rate management - Vlas, Olesea (2015)
The aim of this thesis is to examine the interest rate risk arising from interest rate movements. The theoretical part is oriented on delivering an ample overview of the interest rate general features, interest rate risk and its measurement and hedging systems. The second part is focused on analysing the bank's interest rate exposure from the short term perspective. It is aiming at capturing the bank's net interest income increments using the maturity gap methodology. The final results are summarized in the conclusion.